Conceptualizing business model piloting : An experiential learning process for autonomous solutions - Thomson, Linus; Sjödin, David; Parida, Vinit; Jovanovic, Marin (Elsevier, 2023)
Business model innovation supports manufacturers in the pursuit of new opportunities. However, successfully innovating a new business model presents a significant learning challenge, especially for highly advanced offerings, such as autonomous solutions. Experiential learning approaches, such as business model piloting, are crucial for fine tuning and scaling new business models, yet the current literature fails to adequately examine business model innovation in the context of advanced industrial offerings. In endeavoring to advance current research, we apply a business model piloting lens to advance understanding of how manufacturers engage in business model piloting for autonomous solutions. Our research builds on a multiple case study of piloting initiatives at two manufacturers, involving 32 interviews with senior managers responsible for autonomous-solution business model pilots. This study proposes a business model piloting framework to support manufacturers in overcoming business model innovation challenges. The framework consists of three phases: business model design, business model validation, and business model institutionalization. Each phase includes key business model piloting activities. We also identify three principles that support experiential learning in business model piloting. We contribute to the business model innovation literature by highlighting the strategic and multi-dimensional nature of business model piloting. This process requires simultaneous configuration of novel technologies for value creation and the design of suitable value delivery and capture mechanisms.
Keywords: business model piloting; business model experimentation; digital servitization; digital business model; digital transformation; artificial intelligence; fi=Strateginen johtaminen|en=Strategic Management|